The charge and spin transport properties in hexagonal silicene nanorings. (1st August 2017) - Xu, N; Zhang, H Y; Wu, X Q; Chen, Q; Ding, J W
Abstract: Based on the tight-binding model, charge and spin transport properties of hexagonal silicene rings are investigated within the nonequilibrium Green's function technique. The effects of external electric, magnetic and exchange fields are taken into account. The calculated results reveal that the hexagonal silicene nanorings act as a controllable spin filter. The near-perfect spin polarization can be achieved by adjusting the electric, magnetic and exchange fields. The calculated results offer new possibilities for silicene ring based spin nanodevices.